Preparation method of low-loss high-permeability high-voltage composite material
Patent Information
- Application Number
- CN202611093198.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-22
- Publication Date
- 2026-10-27
AI Technical Summary
该工艺通过高温退火释放应力、降低损耗,可获得更低的损耗与更高的饱和特性;但高压成型极易压裂粉体表面的绝缘包覆层,高温退火又会使高分子粘结剂与绝缘材料发生热分解,导致粉体间绝缘失效、涡流损耗急剧上升,材料表面击穿电压通常仅300V左右;同时绝缘材料选择受限,配方开发难度极大,产品良率低、成本高
1、本发明提供了一种低损耗高磁导率高耐压复合材料制备方法,从材料机理出发,通过将纳米晶成分的非晶粉压制成产品,通过将退火温度设定在纳米晶成分非晶粉纳米晶晶化形成的温度使非晶形核成纳米晶,且该退火温度解决了压制带来的应力,降低了材料的磁滞损耗,进而使该配方损耗较低,又因为退火温度及压制压力较低,保护了钝化材料与胶水,进一步提高了产品的表面绝缘耐压,从而使粉末间涡流损耗得到避免,最终整体性能远大于常规压制工艺及铜铁共烧工艺。
Smart Images

Figure CN122991792A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of soft magnetic functional composite materials and electronic component fabrication technology, specifically a method for preparing a low-loss, high-permeability, and high-pressure-resistant composite material. Background Technology
[0002] As power electronic systems rapidly develop towards higher frequencies, smaller sizes, and higher power densities, power inductors, as core passive components, face increasingly stringent requirements regarding the permeability, loss characteristics, insulation withstand voltage, and temperature stability of their core materials.
[0003] Currently, the mainstream inductor manufacturing processes in the industry fall into two categories, each with its own significant technological bottlenecks: The first type is the traditional molding process: soft magnetic powder is mixed with polymer binders such as epoxy resin and granulated, and then an enameled coil is pre-embedded in a process with a pressure below 9T / cm. 2 The material is formed under pressure at room temperature or by warm pressing, followed by low-temperature curing at around 180°C. The advantages of this process are low molding pressure, intact insulating coating, and good material pressure resistance; however, its disadvantages are significant: low-temperature curing only achieves resin cross-linking and cannot release the internal stress generated during pressing, resulting in high material coercivity, large hysteresis loss, and the powder remaining in its initial amorphous or low permeability state, leading to low effective permeability. Device design requires increasing the number of coil turns, resulting in increased DC resistance and lower overall efficiency.
[0004] The second type is the copper-iron co-firing process: copper sheets are embedded and fired together with soft magnetic powder at 12~24T / cm. 2 High-pressure molding followed by high-temperature annealing at 500-800℃ is a process that releases stress and reduces losses through high-temperature annealing, resulting in lower losses and higher saturation characteristics. However, high-pressure molding easily cracks the insulating coating layer on the powder surface, and high-temperature annealing causes thermal decomposition of the polymer binder and insulating material, leading to insulation failure between powders, a sharp increase in eddy current losses, and a material surface breakdown voltage that is typically only around 300V. At the same time, the selection of insulating materials is limited, formula development is extremely difficult, and product yield is low with high costs.
[0005] In summary, the two existing processes create a performance seesaw where "high withstand voltage results in low permeability and high loss, while low loss results in poor withstand voltage and insulation degradation," which cannot simultaneously meet the triple requirements of low loss, high permeability, and high withstand voltage in high-frequency scenarios.
[0006] Therefore, developing a method for preparing soft magnetic composite materials that can overcome the aforementioned performance contradictions is a core technical problem that urgently needs to be solved in this field. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a method for preparing low-loss, high-permeability, and high-voltage-resistant composite materials. Through the core technical route of "two-step passivation to construct a double-layer insulation and low-temperature crystallization annealing," the invention achieves powder nanocrystallization and stress release while maintaining the integrity of the insulation coating and high voltage resistance. This simultaneously improves permeability and reduces losses, breaking through the performance bottleneck of traditional processes and producing a soft magnetic composite material with excellent properties in all three aspects, suitable for the application requirements of high-frequency, high-power inductors.
[0008] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a low-loss, high-permeability, and high-pressure-resistant composite material includes the following steps: Step S1: First step inorganic passivation The soft magnetic powder and passivating material A solution are added to a sealed ball mill and mixed to form a uniform inorganic passivation film on the powder surface. After removal, the powder is dried and sieved to obtain the first-step passivation powder. The amount of passivating material A added is 0.3% to 0.5% of the mass of the soft magnetic powder. S2: Second step organic coupling passivation The passivation powder and passivation material B solution were mixed and stirred in a sealed ball mill to graft an organic coupling layer onto the surface of the inorganic passivation film. After removal, the mixture was dried and sieved to obtain a double-layer coated passivation powder. The amount of passivation material B added was 0.1% to 0.4% of the mass of the soft magnetic powder. S3: Composite Granulation The double-layer coated passivation powder is mixed with organosilicon resin binder and organic solvent, stirred evenly, granulated and dried at low temperature to obtain soft magnetic composite powder. S4: Warm pressing The finished powder is placed into a mold and cold-pressed under mold heating conditions to obtain a magnetic blank green blank; S5: Low-temperature crystallization annealing The green blank is placed in a nitrogen-protected atmosphere furnace and annealed at 400~480℃ for 30~90 minutes to allow the amorphous powder to precipitate a nanocrystalline phase and release the compressive stress, ultimately obtaining a low-loss, high-permeability, and high-pressure-resistant soft magnetic composite material.
[0009] Further, in step S1, the soft magnetic powder is one or more of the following: iron-based amorphous powder, iron-based nanocrystalline amorphous powder, cobalt-based nanocrystalline amorphous powder, nickel-based nanocrystalline amorphous powder, gas-atomized iron-nickel powder, iron-silicon-aluminum powder, and iron-silicon powder; the D50 particle size of the soft magnetic powder is 10~20μm.
[0010] Further, in step S1, the passivating material A is one or a mixture of phosphoric acid, phosphate, and nitrate; the passivating material A solution uses acetone as a solvent, and the amount of solvent added is 10 parts of the mass of the soft magnetic powder; the ball milling speed is 200 r / min, and the mixing time is 10 min; the drying conditions are 60℃ for 60 min, and after drying, it is passed through a 100-mesh sieve.
[0011] Further, in step S2, the passivating material B is one or a mixture of several of vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and anilinemethyltrimethoxysilane; the passivating material B solution uses a mixture of anhydrous ethanol and pure water as a solvent, wherein 6 parts are anhydrous ethanol and 2 parts are pure water; the ball milling speed is 200 r / min and the mixing time is 10 min; the drying conditions are 130℃ for 60 min, and after drying, it is passed through a 100-mesh sieve.
[0012] Further, in step S3, the amount of silicone resin added is 4% of the mass of the double-layer coated passivation powder; the organic solvent is acetone; after mixing and stirring evenly, granulation is performed by swinging, and the drying conditions are 60℃ for 60 minutes to remove residual solvent.
[0013] Furthermore, in step S4, the molding process employs a warm-press process, with a mold temperature of 140°C and a molding unit pressure of 6T / cm. 2 The holding time is 10~30s; the green blank is a magnetic ring or inductive magnet with uniform density and no delamination or cracking.
[0014] Furthermore, in step S5, the annealing temperature is precisely matched to the initial crystallization temperature of the nanocrystals of the soft magnetic powder, and the annealing process simultaneously achieves a triple effect: ① Uniform nanocrystalline grains precipitate in an amorphous matrix, which improves saturation magnetic induction and permeability and reduces hysteresis loss; ②Release the internal stress generated during the thermoforming process, reduce coercivity, and further reduce losses; ③ The annealing temperature is lower than the thermal decomposition temperature of the insulating coating layer, so that the double-layer insulation structure remains intact and the material maintains high insulation withstand voltage performance.
[0015] Furthermore, the annealing process in step S5 is specifically as follows: the temperature is increased to 450°C at a rate of 3~5°C / min, held for 60min, and then naturally cooled with the furnace; high-purity nitrogen is introduced for protection throughout the process, and the oxygen content is ≤100ppm.
[0016] Furthermore, in the soft magnetic composite material prepared by the method, each magnetic powder particle has a double-layer insulating coating structure of "inorganic passivation layer and organic coupling layer" on its surface; the effective magnetic permeability of the material is increased by more than 50% compared with the traditional curing process at 180℃, the loss is reduced by more than 40% at 500kHz / 50mT, and the surface insulation breakdown voltage is ≥900V.
[0017] Furthermore, the soft magnetic composite material is applied to high-frequency molded power inductors, integrally molded inductors, and EMI filter devices, adapting to high-frequency, high-power scenarios such as new energy vehicle electronics, consumer fast charging, and server power supplies.
[0018] This invention provides a method for preparing a low-loss, high-permeability, and high-pressure-resistant composite material. It has the following beneficial effects: 1. This invention provides a method for preparing a low-loss, high-permeability, and high-pressure-resistant composite material. Starting from the material mechanism, the amorphous powder of nanocrystalline components is pressed into a product. By setting the annealing temperature at the temperature at which the amorphous powder of nanocrystalline components crystallizes, the amorphous nucleation of amorphous components into nanocrystalline is achieved. This annealing temperature solves the stress caused by pressing and reduces the magnetic hysteresis loss of the material, thereby making the formula have low loss. Furthermore, because the annealing temperature and pressing pressure are low, the passivation material and adhesive are protected, further improving the surface insulation and pressure resistance of the product. This avoids eddy current loss between powders, and the final overall performance is far superior to conventional pressing processes and copper-iron co-firing processes.
[0019] 2. This invention provides a method for preparing low-loss, high-permeability, and high-voltage-resistant composite materials. It employs a double-layer insulating coating structure with synergistic effects. The inorganic layer is resistant to high temperatures, while the organic layer compensates for defects. After annealing at 450°C, the insulation structure is not significantly damaged, and the breakdown voltage retention rate is ≥60%. The overall process is compatible with existing molded inductor production lines, eliminating the need for additional ultra-high voltage molding equipment and ultra-high temperature annealing furnaces. The annealing temperature is low, energy consumption is low, and the costs of powder and coating materials are controllable. The overall manufacturing cost is only about 60% of that of the copper-iron co-firing process, making it suitable for large-scale mass production.
[0020] 3. This invention provides a method for preparing low-loss, high-permeability, and high-voltage-resistant composite materials. This process is adaptable to various mainstream soft magnetic powders such as iron-based amorphous materials, iron-based / cobalt-based / nickel-based nanocrystalline amorphous materials, iron-nickel, iron-silicon-aluminum, and iron-silicon. The powder system can be flexibly selected according to different performance requirements, covering a full range of application scenarios from consumer electronics to automotive electronics. The high permeability can reduce the number of turns in the inductor coil, reduce DC resistance, and improve device efficiency; the low loss can reduce device heat generation and increase power density; and the high voltage resistance can improve device reliability and insulation level, making it particularly suitable for new energy vehicle electronic scenarios with high-voltage input and high-frequency operation. Attached Figure Description
[0021] Figure 1This is a schematic diagram of the overall process flow for the preparation method of the low-loss, high-permeability, and high-pressure-resistant composite material of the present invention. Figure 2 This is a schematic diagram of the microstructure of the double-layer coated soft magnetic particles of the present invention; Figure 3 This is a bar chart comparing the magnetic permeability, loss, and withstand voltage performance of different process schemes of the present invention. Detailed Implementation
[0022] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it. Furthermore, it should be noted that, for ease of description, the accompanying drawings show only the parts relevant to the present invention, and not all of the structures.
[0023] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0024] like Figures 1-3 As shown, this embodiment of the invention provides a method for preparing a low-loss, high-permeability, and high-pressure-resistant composite material, comprising the following steps: Step S1: First step inorganic passivation The soft magnetic powder and passivating material A solution are added to a sealed ball mill and mixed to form a uniform inorganic passivation film on the powder surface. After removal, the powder is dried and sieved to obtain the first-step passivation powder. The amount of passivating material A added is 0.3% to 0.5% of the mass of the soft magnetic powder. S2: Second step organic coupling passivation The passivation powder and passivation material B solution were mixed and stirred in a sealed ball mill to graft an organic coupling layer onto the surface of the inorganic passivation film. After removal, the mixture was dried and sieved to obtain a double-layer coated passivation powder. The amount of passivation material B added was 0.1% to 0.4% of the mass of the soft magnetic powder. S3: Composite Granulation The double-layer coated passivation powder is mixed with organosilicon resin binder and organic solvent, stirred evenly, granulated and dried at low temperature to obtain soft magnetic composite powder. S4: Warm pressing The finished powder is placed into a mold and cold-pressed under mold heating conditions to obtain a magnetic blank green blank; S5: Low-temperature crystallization annealing The green blank is placed in a nitrogen-protected atmosphere furnace and annealed at 400~480℃ for 30~90 minutes to allow the amorphous powder to precipitate a nanocrystalline phase and release the compressive stress, ultimately obtaining a low-loss, high-permeability, and high-pressure-resistant soft magnetic composite material.
[0025] The soft magnetic composite material prepared by this method is made by mixing the following raw materials in parts by weight: Iron powder: 100 portions; Passivating material A: 0.3-0.5 wt%; Passivating material B: 0.1-0.4 wt%; Preferably, the iron powder material is one of the following: amorphous powder FexSiyBz, iron-based nanocrystalline amorphous powder, cobalt-based nanocrystalline amorphous powder, nickel-based nanocrystalline amorphous powder, gas-atomized iron-nickel, iron-silicon-aluminum, and iron-silicon powder. Preferably, the passivating material A is one or more of phosphoric acid, phosphate, and nitrate; Preferably, the passivating material B is one or a mixture of several of vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and anilinemethyltrimethoxysilane.
[0026] In the soft magnetic composite material prepared by this method, each magnetic powder particle has a double-layer insulating coating structure consisting of an inorganic passivation layer and an organic coupling layer. The material's effective magnetic permeability is increased by more than 50% compared to the traditional curing process at 180℃, the loss is reduced by more than 40% at 500kHz / 50mT, and the surface insulation breakdown voltage is ≥900V. This soft magnetic composite material is used in high-frequency molded power inductors, integrally molded inductors, and EMI filter devices, and is suitable for high-frequency and high-power scenarios such as new energy vehicle electronics, consumer fast charging, and server power supplies.
[0027] The present invention will be further described in detail below with reference to specific embodiments and comparative examples. The embodiments are only used to explain the technical solutions of the present invention and do not limit the scope of protection of the present invention.
[0028] Test materials: Iron-based amorphous powder QAM-C9: D50=15μm, Huijin Technology; Iron-based nanocrystalline amorphous powders QNM-NC1 and QNM-NC2: D50=15μm, Huijin Technology; Cobalt-based nanocrystalline amorphous powder QNM-NC21: D50=15μm, Huijin Technology; Nickel-based nanocrystalline amorphous powder QNM-NC31: D50=15μm, Huijin Technology; Atomized FeNi50 powder: D50=15μm, AnTai Technology; Phosphoric acid: analytical grade, concentration 85%; γ-aminopropyltriethoxysilane (KH550): Industrial grade; Methyl silicone resin: solid content 50%; Acetone, anhydrous ethanol: analytical grade; High-purity nitrogen: purity ≥ 99.999%.
[0029] Test equipment: Planetary ball mill, electric heating blast oven, high-speed mixer, gyratory granulator, four-column hydraulic thermostatic press, tubular atmosphere annealing furnace, Hioki IM3536 impedance analyzer, Iwasaki SY-8218 loss tester, Chroma19073 withstand voltage tester.
[0030] Test standards and conditions: Effective permeability: The test magnetic ring has an outer diameter of 14 mm, an inner diameter of 8 mm, and a thickness of 3 mm. The inductance value was calculated at 1 MHz and the average value of 5 samples was taken. Core loss: Tested at 500kHz and 50mT, and the average value of 5 samples was taken; Surface insulation breakdown voltage: The voltage value when the probe spacing is 1.5mm and the leakage current IR ≤ 0.1MΩ, based on the statistical values of 30 samples.
[0031] Example 1: Amorphous powder system This embodiment uses iron-based amorphous powder QAM-C9 as raw material, and the specific preparation steps are as follows: S1: First step, inorganic passivation Weigh 100g of amorphous powder and put it into a ball mill jar. Add 0.4g of phosphoric acid and 10g of acetone to prepare a passivation solution. After sealing, ball mill the mixture at 200r / min for 10min. After removing the mixture, spread it evenly on a tray and place it in an oven at 60℃ for 60min to dry. After drying, sieve it through a 100-mesh sieve to obtain the first step passivation powder.
[0032] S2: Second step organic coupling passivation All the passivation powder from the first step was placed back into the ball mill jar, and a coupling agent solution prepared with 0.25g KH550, 6g anhydrous ethanol, and 2g pure water was added. After sealing, the mixture was ball milled at 200r / min for 10min. After removing it, it was placed in an oven at 130℃ for 60min to dry. The powder was then sieved through a 100-mesh sieve to obtain double-layer coated passivation powder.
[0033] S3: Composite Granulation Add 4g of silicone resin and an appropriate amount of acetone solvent to the double-layer coated powder, stir at high speed for 15 minutes until uniform; after shaking granulation, dry at 60℃ for 60 minutes to obtain the finished composite powder.
[0034] S4: Warm pressing The finished powder is placed into a magnetic ring mold with an outer diameter of 14mm and an inner diameter of 8mm. The mold is preheated to 140℃ and then subjected to a flow rate of 6T / cm. 2 The unit pressure is held for 20 seconds to press into a green magnetic ring.
[0035] S5: Low-temperature crystallization annealing The green blank is placed in a tube annealing furnace, high-purity nitrogen is introduced, and the temperature is raised to 450°C at 4°C / min and held for 60 min. Then it is naturally cooled to room temperature in the furnace to obtain the finished magnetic ring.
[0036] Example 2: Iron-based nanocrystalline NC1 system In this embodiment, the iron-based nanocrystalline amorphous powder QNM-NC1 is used as the raw material, and the rest of the preparation process and parameters are exactly the same as in Example 1.
[0037] Example 3: Iron-based nanocrystalline NC2 system In this embodiment, the iron-based nanocrystalline amorphous powder QNM-NC2 is used as the raw material, and the rest of the preparation process and parameters are exactly the same as in Example 1.
[0038] Example 4: Cobalt-based nanocrystalline system In this embodiment, cobalt-based nanocrystalline amorphous powder QNM-NC21 is used as raw material, and the rest of the preparation process and parameters are exactly the same as in Example 1.
[0039] Example 5: Nickel-based nanocrystalline system In this embodiment, nickel-based nanocrystalline amorphous powder QNM-NC31 was used as the raw material, and the rest of the preparation process and parameters were exactly the same as in Example 1.
[0040] Example 6: Iron-nickel powder system This embodiment uses gas-atomized FeNi50 powder as raw material, and the rest of the preparation process and parameters are exactly the same as in Example 1.
[0041] Comparative Examples 1-6: Traditional Low-Temperature Curing Process for Molding Comparative Examples 1-6 used the same powder and two-step passivation, granulation, and molding process as Examples 1-6, except that the annealing process was replaced with the traditional 180℃ heat preservation for 1 hour curing, and all other parameters were completely the same.
[0042] Comparative Examples 7-12: High-Temperature Annealing Process for Co-firing of Copper and Iron Comparative Examples 7-12 used the same powder as Examples 1-6 (only for conventional single-layer insulation coating), and the molding process was 16T / cm. 2 The process involves pressing under high pressure at room temperature, followed by nitrogen annealing at 700℃ for 1 hour to simulate the conditions of copper-iron co-firing.
[0043] Comparative Example 13: Iron-nickel powder annealed at a higher temperature This comparative example uses FeNi50 powder, which is formed under high pressure and then annealed at 730℃ for 1 hour. The rest is the same as comparative example 12.
[0044] Performance Testing and Results Analysis The soft magnetic composite powder prepared in the above examples and comparative examples was placed into a magnetic ring mold with an outer diameter of 14 mm and an inner diameter of 8 mm. Magnetic rings were prepared according to the different sample preparation conditions in the table below. The magnetic ring sample preparation scheme is shown in Table 1 below: Table 1 Magnetic Ring Sample Preparation Scheme The magnetic rings were annealed under different annealing conditions in a nitrogen atmosphere. After annealing, the characteristics, surface breakdown voltage, and losses of the magnetic rings were tested. The test results are shown in Table 2 below. Table 2. Powder Material Magnetic Ring Characteristic Data Results analysis: 1. Comparison with traditional molding processes The effective permeability and loss performance of the embodiments of the present invention are significantly better than those of Comparative Examples 1-6. Taking the iron-based nanocrystals of Example 2 as an example, the permeability increased from 33 to 80, an increase of 142%; the loss decreased from 4300 to 1000 mW / cm. 3 The voltage decreased by 76.7%; although the breakdown voltage decreased slightly, it remained at a relatively high level of 1100V, fully meeting the device insulation requirements. This demonstrates that 450℃ crystallization annealing effectively achieved nanocrystal precipitation and stress release, significantly improving magnetic properties.
[0045] 2. Comparison with copper-iron co-firing process Although some systems produced by the copper-iron co-firing process exhibit high permeability, their breakdown voltage is generally only around 300V, resulting in extremely poor insulation performance. Furthermore, most systems actually have higher losses. In Comparative Example 13, after increasing the annealing temperature, the permeability continued to rise, but the withstand voltage plummeted to 50V, and the loss soared to 15000mW / cm². 3 This indicates that the high temperature severely damaged the insulation structure, causing uncontrolled eddy current losses.
[0046] The breakdown voltage of the embodiments of the present invention is generally between 900 and 1300V, which is 3 to 4 times that of copper-iron co-fired systems. At the same time, the loss is much lower than that of copper-iron co-fired amorphous / nanocrystalline systems, and the overall performance advantage is extremely significant.
[0047] 3. Compatibility with different powder systems This process significantly improves the performance of all tested powders, with the cobalt-based nanocrystalline system exhibiting the best overall performance and a loss as low as 800 mW / cm³. 3 The magnetic permeability is 90 and the withstand voltage is 1100V. The iron-based nanocrystalline system has the highest cost performance and is suitable for large-scale applications. The improvement of the iron-nickel system is relatively smaller, but it is still significantly better than traditional molding. This proves that the process of this invention has broad powder compatibility.
[0048] 4. Verification of the effect of two-step passivation If the second step of organic coupling passivation is omitted, the breakdown voltage will decrease by 20% to 30% under the same annealing conditions, proving that the double-layer coating structure plays a key role in maintaining the insulation withstand voltage after annealing. The inorganic layer provides a high-temperature resistant skeleton, while the organic layer fills defects and improves bonding strength. The two work together to ensure insulation performance.
[0049] The above embodiments and comparative examples fully verify the technical effectiveness of the method of the present invention: by constructing a double-layer insulation structure through two-step passivation of "inorganic and organic", combined with low-temperature crystallization annealing at 400~480℃, the performance bottleneck of traditional processes has been successfully broken, and the simultaneous excellence of low loss, high magnetic permeability and high withstand voltage has been achieved.
[0050] This invention features a mature process, controllable cost, and compatibility with existing production lines. It provides a brand-new technical solution for high-frequency, high-power soft magnetic composite materials and has extremely high industrial application value and market promotion prospects.
[0051] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A method for preparing a low-loss, high-permeability, and high-pressure-resistant composite material, characterized in that, Includes the following steps: Step S1: First step inorganic passivation The soft magnetic powder and passivating material A solution are added to a sealed ball mill and mixed to form a uniform inorganic passivation film on the powder surface. After removal, the powder is dried and sieved to obtain the first-step passivation powder. The amount of passivating material A added is 0.3% to 0.5% of the mass of the soft magnetic powder. S2: Second step organic coupling passivation The passivation powder and passivation material B solution were mixed and stirred in a sealed ball mill to graft an organic coupling layer onto the surface of the inorganic passivation film. After removal, the mixture was dried and sieved to obtain a double-layer coated passivation powder. The amount of passivation material B added was 0.1% to 0.4% of the mass of the soft magnetic powder. S3: Composite Granulation The double-layer coated passivation powder is mixed with organosilicon resin binder and organic solvent, stirred evenly, granulated and dried at low temperature to obtain soft magnetic composite powder. S4: Warm pressing The finished powder is placed into a mold and cold-pressed under mold heating conditions to obtain a magnetic blank green blank; S5: Low-temperature crystallization annealing The green blank is placed in a nitrogen protective atmosphere furnace and annealed at 400~480℃ for 30~90min to allow the amorphous powder to precipitate a nanocrystalline phase and release the compressive stress, ultimately obtaining a low-loss, high-permeability, and high-pressure-resistant soft magnetic composite material.
2. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, In step S1, the soft magnetic powder is one or more of the following: iron-based amorphous powder, iron-based nanocrystalline amorphous powder, cobalt-based nanocrystalline amorphous powder, nickel-based nanocrystalline amorphous powder, gas-atomized iron-nickel powder, iron-silicon-aluminum powder, and iron-silicon powder; the D50 particle size of the soft magnetic powder is 10~20μm.
3. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, In step S1, the passivating material A is one or a mixture of phosphoric acid, phosphate, and nitrate; the passivating material A solution uses acetone as a solvent, and the amount of solvent added is 10 parts of the mass of the soft magnetic powder; the ball milling speed is 200 r / min, and the mixing time is 10 min; the drying conditions are 60℃ for 60 min, and after drying, it is passed through a 100-mesh sieve.
4. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, In step S2, the passivating material B is one or a mixture of several of vinyltriethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and anilinemethyltrimethoxysilane; the passivating material B solution uses a mixture of anhydrous ethanol and pure water as a solvent, wherein there are 6 parts of anhydrous ethanol and 2 parts of pure water; the ball milling speed is 200 r / min and the mixing time is 10 min; the drying conditions are 130℃ for 60 min and then passed through a 100-mesh sieve.
5. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, In step S3, the amount of silicone resin added is 4% of the mass of the double-layer coated passivation powder; the organic solvent is acetone; after mixing and stirring evenly, the mixture is granulated by swinging, and the drying conditions are 60℃ for 60 minutes to remove residual solvent.
6. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, In step S4, the molding process employs a warm-press process, with a mold temperature of 140℃ and a molding unit pressure of 6T / cm. 2 The holding time is 10~30s; the green blank is a magnetic ring or inductive magnet with uniform density and no delamination or cracking.
7. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, In step S5, the annealing temperature is precisely matched to the initial crystallization temperature of the nanocrystals of the soft magnetic powder, and the annealing process simultaneously achieves a triple effect: ① Uniform nanocrystalline grains precipitate in an amorphous matrix, which improves saturation magnetic induction and permeability and reduces hysteresis loss; ②Release the internal stress generated during the thermoforming process, reduce coercivity, and further reduce losses; ③ The annealing temperature is lower than the thermal decomposition temperature of the insulating coating layer, so that the double-layer insulation structure remains intact and the material maintains high insulation withstand voltage performance.
8. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, The annealing process in step S5 is as follows: the temperature is increased to 450°C at a rate of 3~5°C / min, held for 60min, and then naturally cooled with the furnace; high-purity nitrogen is introduced for protection throughout the process, and the oxygen content is ≤100ppm.
9. The method for preparing low-loss, high-permeability, and high-pressure-resistant composite materials according to claim 1, characterized in that, The soft magnetic composite material prepared by the method has a double-layer insulating coating structure of "inorganic passivation layer and organic coupling layer" on the surface of each magnetic powder particle; the effective magnetic permeability of the material is increased by more than 50% compared with the traditional curing process at 180℃, the loss is reduced by more than 40% at 500kHz / 50mT, and the surface insulation breakdown voltage is ≥900V.